How job crafting influences work meaningfulness in coworking spaces - Berdicchia, Domenico; Mazzardo, Elena; Fortezza, Fulvio; Masino, Giovanni (Piccola Impresa / Small Business, 2025)
Purpose. Coworking spaces are emerging as a new organizational archetype involving freelancers, independent professionals, entrepreneurs, and corporate employees. Specialized providers design these innovative environments to encourage continuous collaboration and knowledge sharing among peers. However, to maximize their systematic encounters with like-minded individuals and achieve valuable outcomes, users are required to self-regulate their behavior daily. This investigation examines the role that proactive behaviors and the sense of job control have in increasing the meaning coworking users associate with their jobs as a key value indicator. Design/methodology/approach. The present research is based on a quantitative study that involved 167 coworking users in 42 different coworking spaces in Italy. Findings. The results show that approach job crafting behaviors positively influence work meaningfulness and that said relationship is strengthened by the job control individuals have. Practical and social implications. Our research offers important managerial implications, giving coworking providers the tools to make their space more engaging by promoting proactive behaviors and improving the knowledge of users about how to make the best of their working experience. Originality of the study. Such findings broaden the literature on coworking spaces, currently underexplored, and underline the importance of investigating, at the same time, individual factors and contextual elements to better understand the nature of work and its outcomes in these spaces.